Morphological effect of side chain on H3O+ transfer inside polymer electrolyte membranes across polymeric chain via molecular dynamics simulation - JinHyeok Cha (Nature Portfolio, 2020)
Abstract Performance and durability of polymer electrolyte membrane are critical to fuel cell quality. As fuel cell vehicles become increasingly popular, membrane fundamentals must be understood in detail. Here, this study used molecular dynamic simulations to explore the morphological effects of perfluorosulfonic acid (PFSA)-based membranes on ionic conductivity. In particular, I developed an intuitive quantitative approach focusing principally on hydronium adsorbing to, and desorbing from, negatively charged sulfonate groups, while conventional ionic conductivity calculations featured the use of mean square displacements that included natural atomic vibrations. The results revealed that shorter side-chains caused more hydroniums to enter the conductive state, associated with higher ion conductivity. In addition, the hydronium path tracking showed that shorter side-chains allowed hydroniums to move among host groups, facilitating chain adsorption, in agreement with a mechanism suggested in earlier studies.